Materialities and disability trajectories in universities (Praxis Educativa, 2026)
The article examines the university trajectories of students with disabilities in Chilean higher education from a critical‑materialist and post‑qualitative perspective. In a context of sustained enrollment growth, it analyzes the tensions between inclusion policies and the persistence of ableist logics that continue to structure institutional practices, affecting students’ retention, participation, and graduation. Drawing on an autobiographical workshop grounded in the production of materialities—such as collages, cartes de visite, and other artifacts—the study explores how disability is configured as a relational effect of assemblages among bodies, objects, infrastructures, normative discourses, affects, and academic temporalities. The findings show that the university emerges simultaneously as a horizon of possibility and as a space of restriction, where myths and processes of normalization and invisibilization operate. Nevertheless, the materialities produced function as devices of creative resistance that enable the imagination of possible futures and alternative ways of inhabiting the university space.
Keywords: Disabilities; Higher Education; Ableism; New Materialisms; Inclusion